Dual‐Functional Nonmetallic Plasmonic Hybrids with Three‐Order Enhanced Upconversion Emission and Photothermal Bio‐Therapy. Issue 11 (5th August 2022) - Li, Juan; Liu, Lu; Chen, Xueqin; Lu, Changhai; Zhang, Haipeng; Li, Baojun; Xue, Can; Lou, Zaizhu
Abstract: Plasmonic semiconductor nanoparticles (NPs) with wide‐range tailorable localized surface plasmon resonance (LSPR) hold exciting prospects on optical signal amplification. In this work, by precisely controlling oxygen vacancies around W atoms, plasmonic bismuth tungstate Bi2 WO6 (BWO) nanosheets are constructed to enhance emission of Yb 3+ /Er 3+ co‐doped NaYF4 upconversion nanoparticles (UCNPs). In the optimal conditions, the UCNPs/BWO‐2 hybrids exhibit over three‐order (1260‐fold) enhancement selectively on the 520 nm emission owing to the strong LSPR‐induced electrical field and photothermal effect. Moreover, it is found that the highly efficient emission of UCNPs/BWO‐2 allows it to act as a thermometer to monitor the real‐time local temperature with high absolute sensitivity of 5.8 × 10 −3 K −1 in wide temperature range (up to 990 K). For proof‐of‐concept, the dual functions of plasmonic UCNPs/BWO‐2 hybrids on bioimaging and photothermal therapy for cancer cells are demonstrated that can be completely killed within 5 min under 980 nm irradiation. As far as it is known, this work reaches a new level on UCNPs emission enhancement by plasmonic semiconductor, exceeding most plasmonic metals. Abstract : A new level of three‐order enhancement on upconversion emission is achieved by plasmonic bismuth tungstate (BWO) and upconversion nanoparticles (UCNPs) hybrids owing to the strong localized surface plasmon resonance‐induced electrical field and photothermal effect. The boosted upconversion emission and photothermal effect of plasmonic UCNPs/BWO hybrids make it dual functions on near infrared light‐triggered bioimaging and photothermal therapy of cancer cell.